2011
DOI: 10.1192/bjp.bp.110.090266
|View full text |Cite
|
Sign up to set email alerts
|

Cost utility of behavioural activation delivered by the non-specialist

Abstract: Behavioural activation by non-specialists appears effective in the treatment of depression. We examined incremental cost-effectiveness of behavioural activation (n = 24) v. treatment as usual (n = 23) in a randomised controlled trial. Intention-to-treat analyses indicated a quality-adjusted life-year (QALY) difference in favour of behavioural activation of 0.20 (95% CI 0.01-0.39, P = 0.042), incremental cost-effectiveness ratio of £5756 per QALY and a 97% probability that behavioural activation is more cost-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 18 publications
(22 reference statements)
1
56
0
1
Order By: Relevance
“…Although BA has a higher initial cost, this evened itself out at the 9-month point and then antidepressants became increasingly expensive 39. A further study suggested that the economic benefits of helping people to recover Quality Adjusted Life Years outweighed the service delivery costs 36. This study went on to demonstrate that the costs were the same as ‘treatment as usual’ but with better treatment outcomes.…”
Section: Resultsmentioning
confidence: 84%
“…Although BA has a higher initial cost, this evened itself out at the 9-month point and then antidepressants became increasingly expensive 39. A further study suggested that the economic benefits of helping people to recover Quality Adjusted Life Years outweighed the service delivery costs 36. This study went on to demonstrate that the costs were the same as ‘treatment as usual’ but with better treatment outcomes.…”
Section: Resultsmentioning
confidence: 84%
“…As such treatments are effective at higher levels of depression (Ekers et al, 2008), the fact that they have 'less moving parts', and as such less components to master, may suggest a high level of stability in results when disseminated. Such ideas are starting to show promise in terms of clinical and cost effectiveness (Ekers et al, 2011a(Ekers et al, , 2011b. Results need replication in larger studies across multiple sites and with more therapists to test this hypothesis further.…”
Section: Discussion Of Findingsmentioning
confidence: 96%
“…The treatment was also cost-effective. 25 Given the significant differences in durability of behavioral activation relative to antidepressant medication, recovery could be extended if behavioral activation treatment were provided as an adjunct to routine medication management in psychiatric practice.…”
Section: Contemporary Approachesmentioning
confidence: 99%